An application of climate change ensemble averaging methods to fisheries management - Vrancken, Candysse Amy Louise (Department of Mathematics and Applied Mathematics, 2019)
Fisheries management has a long history, having started gradually in the middle of the 19th century. As the awareness of the importance of managing fisheries increased, the need for fisheries scientists and for methodical research into the dynamics of fish populations arose. The methods and science used to manage fisheries have continued to grow and improve since then. Discussions related to climate change have also been ongoing for a long time, resulting in the field of climate change science which focuses on the various components of the natural environment. Both fisheries management and climate change science have similar main objectives, and overall methods for achieving those objectives. Those similarities are explored using the example of the South African hake fishery (South Africa’s most valuable fishery) where, as in other fisheries, problems can occur when an equally weighted average over different assessment models (also termed Operating Models, or OMs) in an ensemble is used. In order to address these problems, a number of methods used in climate change to address similar problems are applied in the case of the hake fishery. The aim is to determine the impact that the application of the model ensemble approaches used in climate change would have had on the recent results obtained from the use of an equally weighted model ensemble average in developing and selecting a management procedure for the South African hake resource. The particular intent of these methods is to reduce any “bias” arising from the use of many models that are rather similar when computing such averages. Chapter 1 contains a brief introduction to the work. Chapter 2 provides a review of a sample of model ensemble types that are used in fisheries management and/or climate change science. Chapter 3 contains a brief history of the management of the South African hake fishery, as well as a detailed description of the components that make up the management procedure used to manage the resource (OMP-2014). The remaining chapters of the dissertation present the data and methods (Chapter 4), results and discussion (Chapter 5) and the conclusions, along with an outline of possible future work (Chapter 6). It seems that weighting the OMs in the Reference Set (RS) ensemble for the South African hake fishery using the climate change model weighting methods, among others, and taking model (dis-)similarity and the goodness of fit of the models to the data into account, would not have had a major impact on the results obtained from using the equally weighted model RS adapted in the development and selection of the OMP-2014 for the resource. Since the time taken for a resource below MSYL to recover to MSYL is a key consideration in the very important Marine Stewardship Council certification process, the impact of different weighting schemes for the RS is of interest in this context. All except one (which is not a recommended method) of the unequally weighted approaches result in projections of the spawning biomass of the more depleted deep-water hake species (M. paradoxus) reaching MSYL at the same time, or a year later, than the equally weighted OMP-2014 projection. The differences arising from the different weighting approaches are therefore not substantial for the South African hake fishery. Hence, although these climate change weighting methods can be applied in this fisheries management context, the weights they produced did not add considerable value to the equally weighted average method used currently for South African hake. However, the object here was only to illustrate these approaches. It could well be that for other fisheries, the weighting scheme could have a greater effect on the eventual results and decisions. The weighting of individual models in an ensemble continues to be of increasing interest in many different fields, including fisheries management and climate change. A continued investigation into other weighting methods that may impact the selection of OMPs for the South African hake and other fisheries is certainly warranted.